Partisipasi Masyarakat Desa dalam Pembangunan (Studi di Desa Amasara Kecamatan Baito Kabupaten Konawe Selatan) - Yunitawati Lampasa (LP3M Universitas Muhammadiyah Kendari, 2022)
This study aims to see the participation of rural communities in development in Amasara Village, Baito District, South Konawe Regency. This study uses a qualitative descriptive method through direct interviews with informants. The informants in this study consisted of 8 people consisting of the village head, village secretary, Kaur (Head of Affairs) development and 5 people from the community. The results showed that the village community in development in Amasara Village, Baito District, South Konawe Regency was very involved, which can be seen from the involvement of the Amasara Village community which when starting from development planning through the Musrembang, the Amasara village community was always present and gave opinions related to the development program that was carried out. will be carried out in their village and in the process of implementing development the Amasara village community is always directly involved, for example, during the construction of a farm road, all communities are involved, for example, someone cuts the weeds around the construction of a farm road. However, not only the fathers who were involved but the mothers also participated in the construction by preparing various foods and drinks during the implementation of the construction.